Nationwide indicators reflecting the current problems of the agricultural landscape in Slovakia: Large agricultural parcels, farm size structure and share of woody vegetation - Lieskovský, Juraj; Špulerová , Jana; Gašparovičová , Petra; Rusňák , Tormáš; Halabuk , Andrej (TÁJÖKOLÓGIAI LAPOK, 2023)
The main problems of the agricultural landscape in Slovakia are the largest parcels in the EU, the share of agricultural land managed by large agro-holdings, and the low proportion of woody vegetation. The authors have analysed these issues using agricultural beneficiary data and remote sensing products. The parcel size and farm sizes were analysed from agricultural beneficiaries’ data, woody vegetation was analysed from the combined layer of Copernicus products and data from the Land Parcel Identification System. Regarding all three indicators, the situation is more problematic in the lowlands and partially in hilly areas. The proposed indicators could be applied to assess the impact of the new CAP (2023-2027), which supports the reduction of parcel size, improves conditions for small and medium farmers, and improves the share of green infrastructure in agricultural landscapes.